The concept of S.M.Voronin in the problem of comparisons of deterministic and random computation in the same terms - Temirgaliyev Н. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2019)
The paper was devoted to propose of S.M.Voronin to evaluate the quality of deterministic and non-deterministic calculation methods in theoretical and practical aspects through probabilistic measures on functional classes in the same language .